Public school teachers' knowledge about management of traumatic dental injuries - Martins, Christine Men [UNESP]; Men, Suely Rui; Pavan, ângelo José; Pavan, Nair Narumi Orita; Gomes-Filho, João Eduardo [UNESP] (My University, 2014)
Introduction: Dental trauma frequently occurs in childhood, especially at school settings. For this reason, it is important that teachers and school staff know how to react when faced with dental trauma, particularly because the faster the dental intervention, the better the dental prognosis. Objective: The aim of this study was to assess public school teachers' knowledge about emergency management of dental trauma. Methods: Forty teachers from a Brazilian public school and a day-care center were interviewed. They answered a questionnaire which aimed to identify their profile; their knowledge about first aid, including dental trauma; the most prevalent type of injury; and how to manage them. Results: Out of 40 teachers, only 65% had received first aid training, and only 52% had received training in emergency management of dental trauma. A total of 40% had already witnessed cases of dental trauma at school and the majority of them (55%) were unaware of how often they occur. A significant number of people are not sure about how to react when faced with tooth crown fracture and avulsion. Conclusion: The present study showed that public school teachers' knowledge about emergency management of dental trauma is insufficient. Educational programs, explanatory lectures and training should be conducted to prepare professionals who are the first to face dental trauma in schools.
Keywords: Dental trauma; Knowledge management for health research; School health services